Analysis of the role of Higher Education in the Belt and Road Initiative with particular focus on Central Asia: Concept, instruments, and practices - Daulet, A.; Amangeldy, D. ("M. Narikbayev KAZGUU University". Nur-Sultan, 2020)
This thesis investigates role of higher education in the Belt and Road Initiative of China. The main aspect of BRI is that China develops economic, cultural, political influence at the world level us. “People to people exchange” is one of five pillars of BRI. Higher education is important from this pillar’s perspective because the future generations will create and develop exchanges between countries. So, that people who go to study abroad receive experience from other countries and in the future could use the knowledge gained to develop their country. Students have the chance to study abroad at the expense of the state - this is an investment in the future through higher education. Based on this premise, this study will highlight how BRI integrates higher education as one of priority areas for the development of the initiative. It includes thorough analysis of three higher education-related projects linked to BRI: Universities role in creation of knowledge on BRI (case of Tongji University), use of higher education institutes for promoting BRI (Confucius Institutes), and fostering world class Universities (Double First-class University Plan). Thesis also provides substantial number of examples of BRI implementation from Central Asian region. This thesis thus highlights the function of BRI as a framework to develop and share knowledge, and improve intercultural communication
Keywords: The Belt and Road Initiative, Central Asia, higher education, people to people exchange, Kazakhstan and China, cooperation, science and technology